(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
We all know that the word "geography" is not only "spatial" or "territorial" as a result of the introduction of geoinformatics and geographic information system (GIS) under the influence of information technologies, that is, in natural sciences. First of all, this concept expresses the complex and systematic characteristics of the research approach. To date, geographic information systems are used in several areas. In particular, it can be widely used in the field of ecology.